2002
DOI: 10.1007/s00464-001-9164-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced acute phase response after laparoscopic total extraperitoneal bilateral hernia repair compared to open repair with the Stoppa procedure

Abstract: The acute phase inflammatory response in clearly more active after the open Stoppa procedure than after TEPP, indicating that the former is associated with increased tissue trauma. This may play a role in the earlier recovery seen after the TEPP procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
(23 reference statements)
4
25
0
Order By: Relevance
“…Our findings are in agreement with the literature, which shows that procedures of similar invasiveness, e.g., hernia repair or urologic surgery, are capable of inducing enough stress to reveal a difference between laparoscopy and laparotomy [43,57].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings are in agreement with the literature, which shows that procedures of similar invasiveness, e.g., hernia repair or urologic surgery, are capable of inducing enough stress to reveal a difference between laparoscopy and laparotomy [43,57].…”
Section: Discussionsupporting
confidence: 83%
“…Many studies comparing laparoscopic and open approaches in the management of cholelithiasis [1,8,21,24,33,54], inguinal hernia [57], urological diseases [20,29,43], and morbid obesity [45,63] showed that minimally invasive techniques were connected with less release of inflammatory cytokines intraoperatively and postoperatively. Similar studies of more complicated procedures like colon resections or hysterectomies differ in results.…”
Section: Discussionmentioning
confidence: 99%
“…The results from our study suggest that laparotomy, with its concomitant increased surgical trauma, can safely be avoided in these cases. This could mean less stress response with fewer immunogenous alterations [1,16], thereby also helping to improve outcome in this setting. In our study, nine of 17 patients (54%) could have been diagnosed and adequately treated without laparotomy.…”
Section: Discussionmentioning
confidence: 94%
“…As we have shown, the diagnostic values of laparoscopy and laparotomy are equivalent. Laparoscopy is associated with less operative trauma and a lower systemic stress response than laparotomy [1,16], which is especially important in critically ill patients. Therefore, the indications for diagnostic laparoscopy should be expanded and abdominal inspection performed earlier, so as to enable earlier intervention and improve the outcome in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology has been used previously to justify the use of tissue-sparing techniques, such as laparoscopy in other surgical subspecialties. 69,70 The investigators measured pre-and postoperative values of various acute phase reactant proteins, such as creatine kinase (CK), C-reactive protein (CRP), interleukin (IL)-6, tumour necrosis factor (TNF)-α and IL-1 in 57 patients undergoing THA. They found a significant increase in CK in the posterior approach group compared with the anterior approach group immediately following the procedure as well as cumulatively 2 days after THA.…”
Section: Anterior Versus Posterior Approachmentioning
confidence: 99%